Non-compliance with smoke-free law in public places: a systematic review and meta-analysis of global studies - Daba, Chala; Atamo, Amanuel; Gasheya, Kassahun Ayele; Geto, Abebe Kassa; Gebrehiwot, Mesfin (Frontiers in Public Health, 2024)
Introduction Non-compliance with smoke-free law is one of the determinants of untimely mortality and morbidity globally. Various studies have been conducted on non-compliance with smoke-free law in public places in different parts of the world; however, the findings are inconclusive and significantly dispersed. Moreover, there is a lack of internationally representative data, which hinders the evaluation of ongoing international activities towards smoke-free law. Therefore, this meta-analysis aimed to assess the pooled prevalence of non-compliance with smoke-free law in public places. Methods International electronic databases, such as PubMed/MEDLINE, Science Direct, Cochrane Library, CINAHL, African Journals Online, HINARI, Semantic Scholar, google and Google Scholar were used to retrieve the relevant articles. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA) guidelines. The Higgs I2 statistics were used to determine the heterogeneity of the reviewed articles. The random-effects model with a 95% confidence interval was carried out to estimate the pooled prevalence of non-compliance. Results A total of 23 articles with 25,573,329 study participants were included in this meta-analysis. The overall pooled prevalence of non-compliance with smoke-free law was 48.02% (95% CI: 33.87–62.17). Extreme heterogeneity was observed among the included studies (I2 = 100%; p < 0.000). The highest non-compliance with smoke-free law was noted in hotels (59.4%; 95% CI: 10.5–108.3) followed by homes (56.8%; 95% CI: 33.2–80.4), with statistically significant heterogeneity. Conclusion As the prevalence of non-compliance with smoke-free law is high in public places, it calls for urgent intervention. High non-compliance was found in food and drinking establishments and healthcare facilities. In light of these findings, follow-up of tobacco-free legislation and creating awareness that focused on active smokers particularly in food and drinking establishments is recommended.